2007
DOI: 10.1890/06-1107.1
|View full text |Cite
|
Sign up to set email alerts
|

The Inflationary Effects of Environmental Fluctuations Ensure the Persistence of Sink Metapopulations

Abstract: Under current rates of environmental change many populations may be found in habitats of low quality and low conservation value, creating population sinks. We test recent theory that suggests, surprisingly, that stochastic environmental variability may enhance the long-term persistence of sink metapopulations. Using experimental populations of Paramecium aurelia we show that it is possible for a metapopulation comprised entirely of sink populations to persist for many generations in a random environment. In ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
61
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 45 publications
13
61
1
Order By: Relevance
“…These conclusions do not mirror those of Gonzalez and Holt (2002), Holt et al (2003), Roy et al (2005), Matthews and Gonzalez (2007), where persistence of declining and sink populations subject to immigration has also been studied both theoretically and experimentally. There it is established that, broadly speaking, time-varying vital rates and constant immigration give rise to populations that are in expectation larger than the mean model would suggest.…”
Section: Time-and Spatial-averaged Behaviourcontrasting
confidence: 61%
See 1 more Smart Citation
“…These conclusions do not mirror those of Gonzalez and Holt (2002), Holt et al (2003), Roy et al (2005), Matthews and Gonzalez (2007), where persistence of declining and sink populations subject to immigration has also been studied both theoretically and experimentally. There it is established that, broadly speaking, time-varying vital rates and constant immigration give rise to populations that are in expectation larger than the mean model would suggest.…”
Section: Time-and Spatial-averaged Behaviourcontrasting
confidence: 61%
“…Many populations are in a state of predictable decline in the absence of immigration, or of deliberate bolstering by conservation management strategies (Pulliam, 1988;Gonzalez and Holt, 2002;Holt et al, 2003;Roy et al, 2005;Matthews and Gonzalez, 2007). In many cases, such immigration events vary dramatically in magnitude or structure throughout the lifespan of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Asynchronous temperatures cause subpopulations to experience contrasting conditions, so that large subpopulations can rescue small subpopulations. Matthews & Gonzalez [16] found that red noise and asynchronous temperatures permitted higher Paramecium aurelia densities in metapopulations. rspb.royalsocietypublishing.org Proc R Soc B 280: 20131747…”
Section: Discussionmentioning
confidence: 99%
“…Asynchronous environmental noise reduces synchrony in subpopulation density fluctuations [15]. This can enhance the beneficial effects of red noise and promote metapopulation persistence, because migration from subpopulations at higher densities can rescue subpopulations at lower densities [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This is obvious for weedy species requiring colonization into empty sites after disturbance or pathogens that must infect fresh hosts to replace infected hosts they kill, but the point pertains to any species in spatially open and temporally varying environments. Theoretical models (46) and experiments (47) show that when local populations are linked by dispersal, a positive autocorrelation through time in local growth rates that is to a degree spatially uncorrelated can permit persistence, even if the average growth rate in each patch predicts extinction [and adaptive habitat selection further enhances persistence (48)]. …”
Section: Stitching the Nichementioning
confidence: 99%